2013
DOI: 10.1093/nar/gkt1316
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule analysis ofThermus thermophilusSSB protein dynamics on single-stranded DNA

Abstract: Single-stranded (ss) DNA binding (SSB) proteins play central roles in DNA replication, recombination and repair in all organisms. We previously showed that Escherichia coli (Eco) SSB, a homotetrameric bacterial SSB, undergoes not only rapid ssDNA-binding mode transitions but also one-dimensional diffusion (or migration) while remaining bound to ssDNA. Whereas the majority of bacterial SSB family members function as homotetramers, dimeric SSB proteins were recently discovered in a distinct bacterial lineage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
(117 reference statements)
2
24
0
Order By: Relevance
“…These results show that our method would be very useful for investigating fast dynamics of homodimeric SSBs. In addition, our results together with previous work by Ha and colleagues 46 58 indicate that the diffusional migration or redistribution of SSB on ssDNA is a general phenomenon. The diffusional migration of dr SSB is much faster than that of tetrameric E. coli SSB.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results show that our method would be very useful for investigating fast dynamics of homodimeric SSBs. In addition, our results together with previous work by Ha and colleagues 46 58 indicate that the diffusional migration or redistribution of SSB on ssDNA is a general phenomenon. The diffusional migration of dr SSB is much faster than that of tetrameric E. coli SSB.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Ha and colleagues 46 58 have studied the dynamics of Thermus thermophilus ( tt ) SSB on ssDNA. tt SSB is a homodimeric SSB similar to dr SSB.…”
Section: Discussionmentioning
confidence: 99%
“…It seems difficult to motivate an orders-of-magnitude difference in binding affinity based solely from the presence of additional base stacks, which are likely transiently breaking and reforming. Furthermore, many SSB's such as replication protein A (RPA) and Escherichia coli (Eco) SSB can melt DNA secondary structure while diffusing on long strands of poly dT ( 56 , 57 ). These results appear to be inconsistent, suggesting on the one hand that base stacking can hamper binding, while on the other, these proteins show behavior that is unaffected by DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RPA can bind very tightly to an ssDNA and dissociate rapidly when other SSBs are present in solution (20). Unlike studies (10,15,16,19) that were performed on an infinitely dilute solution, the findings of the study in ref. 20 apply to a wide range of conditions.…”
mentioning
confidence: 94%
“…Recent studies using single-molecule fluorescence resonance energy transfer have endeavored to shed light on the dynamic activity of different types of SSBs, which were earlier thought to form inert complexes with ssDNAs. These studies have shown that the Escherichia coli SSB functions as a sliding platform that migrates on ssDNA (10,15), whereas a homodimeric bacterial SSB from Thermus thermophilus is able to diffuse spontaneously along ssDNA (16). It was reported that the diffusion coefficient of the E. coli SSB along ssDNA is similar to that of transcription factors along dsDNA (17).…”
mentioning
confidence: 99%